BS EN ISO 21219-9. Intelligent transport systems. Traffic and travel information (TTI) via transport protocol experts group, generation 2 (TPEG2). Part 9. Service and network information (TPEG2-SNI) (28th July 2020) - British Standards Institution
No abstract available